TEACHER PROFESSIONAL COMPETENCIES IN DEVELOPING STUDENTS' DISCIPLINE CHARACTER THROUGH INTERACTIVE WORDWALL MEDIA IN NATURAL AND SOCIAL SCIENCE LEARNING IN FOURTH GRADE OF ELEMENTARY SCHOOL - Ruly Via Ratnawati; Ine Kusuma Aryani; Y. Suyitno; Subuh Anggoro (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the professional competence of teachers in developing students' disciplined character through interactive media, Wordwall, in natural and social science learning in elementary schools. The research method is qualitative with a case study design at SDN 1 Bedana. The research subjects were class teachers and fourth-grade students. Data collection techniques through observation, interviews, and documentation. Data analysis used an interactive model that includes data condensation, data presentation, and drawing conclusions. Data validity was tested through source triangulation and technique triangulation to ensure the validity of the research findings. The results show that the professional competence of teachers in natural and social science learning based on Wordwall contributes to strengthening students' disciplined character through learning management that includes mastery of material, planning learning objectives, preparing interactive teaching materials, continuous self-development, and the use of learning technology. The impact is seen in increasing student discipline, which is demonstrated through compliance with rules, consistency in participating in learning, punctuality, and responsibility for the learning process and outcomes. In conclusion, students' disciplined character can be strengthened through good teacher professional skills and the use of Wordwall learning media that is carried out regularly and directed. Therefore, teachers and schools need to optimize its use so that learning is of higher quality and students become more accustomed to being disciplined.